2020
DOI: 10.1088/1361-6560/ab8bf3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of the dose and linear energy transfer (LET) of carbon-ion beams using radiochromic films

Abstract: Radiochromic films are useful as dosimeters in high-precision radiotherapy owing to their high spatial resolution. However, when a particle beam is measured using a radiochromic film, the dose cannot be estimated accurately because the film darkness varies with variations in linear energy transfer (LET). This paper proposes a novel method for estimating the LET and the dose based on the film darkness. In this method, after a high-LET particle beam, such as a carbon-ion beam, was incident on the film, the film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Their applicability in describing physical effects such as the experimental under‐responses is a choice that seems to be detector dependent. For instance, Christensen et al, had shown that track‐averaged LET values were more accurate in predicting the magnitude of proton quenching of plastic scintillators 48 whereas other authors have shown that dose‐averaging was a more accurate measure for other dosimeters such as OSLDs 25 and radiochromic films 26,49 . As such, it is important for us to determine the more accurate averaging scheme (dose‐ or track‐averaging) that is more relevant to BaFBr 0.85 I 0.15 :Eu 2+ dosimeters.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their applicability in describing physical effects such as the experimental under‐responses is a choice that seems to be detector dependent. For instance, Christensen et al, had shown that track‐averaged LET values were more accurate in predicting the magnitude of proton quenching of plastic scintillators 48 whereas other authors have shown that dose‐averaging was a more accurate measure for other dosimeters such as OSLDs 25 and radiochromic films 26,49 . As such, it is important for us to determine the more accurate averaging scheme (dose‐ or track‐averaging) that is more relevant to BaFBr 0.85 I 0.15 :Eu 2+ dosimeters.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Christensen et al, had shown that track-averaged LET values were more accurate in predicting the magnitude of proton quenching of plastic scintillators 48 whereas other authors have shown that dose-averaging was a more accurate measure for other dosimeters such as OSLDs 25 and radiochromic films. 26,49 As such, it is important for us to determine the more accurate averaging scheme (dose-or track-averaging) that is more relevant to BaFBr 0.85 I 0.15 :Eu 2+ dosimeters. From the experimental under-response values of BaFBr 0.85 I 0.15 :Eu 2+ , we attempted to restore the original SOBP curve by normalizing it with their expected under-response [Fig.…”
Section: G Analytical Proton Stopping Power Ratio and Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…The proton therapy community increasingly focuses on the relative biological effectiveness (RBE) and the effect of the linear energy transfer (LET) distributions in treatment plans 1 . Several detectors, such as semiconductors 2 , gas counters 3 , and radiochromic films 4 , have been proposed to measure the LET of hadrons at conventional dose-rates. Nevertheless, dosimetry in hadron beams remains challenging because of the typical under-response due to the ionization quenching of otherwise dose-rate independent detectors 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Radiochromic films are convenient tools widely used for QA measurements [1] . However, the film response of particle beams depends not only on the dose but also on the linear energy transfer (LET) [2] , [3] , [4] , [5] , [6] , [7] , [8] . Regarding the LET dependence known as LET quenching [9] , above 40% variations in film responses have been reported in the LET range of clinical carbon-ion beams [3] .…”
Section: Introductionmentioning
confidence: 99%